2019
DOI: 10.1088/1361-6641/aae4c3
|View full text |Cite
|
Sign up to set email alerts
|

Valence band states in an InAs/AlAsSb multi-quantum well hot carrier absorber

Abstract: In this study, detailed temperature dependent simulations for absorption and photogenerated recombination of hot electrons are compared with experimental data for an InAs/AlAsSb multi-quantum well. The simulations describe the actual photoluminescence (PL) observations accurately; in particular, the room temperature e1-hh1 simulated transition energy of 805 meV closely matches the 798 meV transition energy of the experimental PL spectra, a difference of only 7 meV. Likewise, the expected energy separations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…If electrons and holes are at different temperatures, Eq. (2) is still valid, with related to the temperature of the carrier populations 30,31 . We will consider here, as is usually assumed, that the carrier temperatures are the same.…”
Section: Methodsmentioning
confidence: 99%
“…If electrons and holes are at different temperatures, Eq. (2) is still valid, with related to the temperature of the carrier populations 30,31 . We will consider here, as is usually assumed, that the carrier temperatures are the same.…”
Section: Methodsmentioning
confidence: 99%
“…The same calculation could be performed with different hole and electron temperatures and/or effective masses [10]. Also, it has been experimentally confirmed that in polar semiconductors, electrons (with a much lower effective mass) heat much more than holes [11]. However, considering different electron and hole behaviors makes the interpretation of the results much more difficult, while it does not bring any further insight into this study.…”
Section: Absorptivity: Band Filling and Light Path Enhancementmentioning
confidence: 94%
“…These properties all occur in InAs/AlAs Sb multiple-quantum wells (MQWs), where a hot-carrier distribution is shown along with extended carrier lifetimes as a result of inhibited phonon–phonon interactions 8 . In steady-state photoluminescence (PL), these MQWs have shown evidence of hot carriers 14 , non-monotonic emission energy as a function of lattice temperature due to the complicated valence band structure 15 and even intervalley scattering of electrons to the long-lived L-valley states 16 . Transient absorption directly shows long-lived carriers complementing the evidence of hot carriers and the non-monotonic temperature dependence 8 .…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 1 Schematic of the optical pump and THz probe experimental geometry ( EOS = electro-optic sampling). ( b ) Band structure 15 of the InAs MQW superlattice. The inset shows the band minima and maxima of a single QW with confined energy levels at cm .
…”
Section: Introductionmentioning
confidence: 99%